Analytical detection of influenza A(H3N2)v and other A variant viruses from the USA by rapid influenza diagnostic tests. Issue 4 (18th September 2012) - Balish, Amanda; Garten, Rebecca; Klimov, Alexander; Villanueva, Julie
<x xml:space="preserve">Abstract</x> Please cite this paper as: Balish et al. (2012) Analytical detection of influenza A(H3N2)v and other A variant viruses from the USA by rapid influenza diagnostic tests. Influenza and Other Respiratory Viruses 7(4), 491–496. Background The performance of rapid influenza diagnostic tests (RIDTs) that detect influenza viral nucleoprotein (NP) antigen has been reported to be variable. Recent human infections with variant influenza A viruses that are circulating in pigs prompted the investigation of the analytical reactivity of RIDTs with these variant viruses. Objectives To determine analytical reactivity of seven FDA‐cleared RIDTs with influenza A variant viruses in comparison with the reactivity with recently circulating seasonal influenza A viruses. Methods Tenfold serial dilutions of cell culture–grown seasonal and variant influenza A viruses were prepared and tested in duplicate with seven RIDTs. Results All RIDTs evaluated in this study detected the seasonal influenza A(H3N2) virus, although detection limits varied among assays. All but one examined RIDT identified the influenza A(H1N1)pdm09 virus. However, only four of seven RIDTs detected all influenza A(H3N2)v, A(H1N2)v, and A(H1N1)v viruses. Reduced sensitivity of RIDTs to variant influenza viruses may be due to amino acid differences between the NP proteins of seasonal viruses and the NP proteins from viruses circulating in pigs. Conclusions Clinicians should be aware of the limitations of RIDTs to detect influenza A variant viruses. Specimens from patients with influenza‐like illness in whom H3N2v is suspected should be sent to public health laboratories for additional diagnostic testing.